1997
DOI: 10.1111/1523-1747.ep12319441
|View full text |Cite
|
Sign up to set email alerts
|

Human Collagenase-3 Is Expressed in Malignant Squamous Epithelium of the Skin

Abstract: Co-expression of several members of the matrix metalloproteinase (MMP) family is a characteristic of human carcinomas. To investigate the role of the recently cloned collagenase-3 (MMP-13) in epidermal tumors, we studied samples representing malignant (basal and squamous cell carcinoma, Paget's disease), pre-malignant (Bowen's disease, solar keratosis), and benign (keratoacanthoma, seborrheic keratosis, linear epidermal nevus) tumors. Basal cell carcinomas expressed collagenase-3 mRNA in focal areas of keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
175
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(189 citation statements)
references
References 33 publications
9
175
1
3
Order By: Relevance
“…18,34 Several MMPs are known to process laminin-5g2 in vitro. 44 We have previously shown that in cutaneous SCCs, laminin5g2 is widely distributed along the invasive tumor front 26,41 and thus our current data show that, in general, staining for laminin-5 cannot help in differentiation between keratoacanthoma and SCC. In this work, we found colocalization of laminin-5 and MMP-10, a phenomenon previously reported in squamous and basal cell cancers.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…18,34 Several MMPs are known to process laminin-5g2 in vitro. 44 We have previously shown that in cutaneous SCCs, laminin5g2 is widely distributed along the invasive tumor front 26,41 and thus our current data show that, in general, staining for laminin-5 cannot help in differentiation between keratoacanthoma and SCC. In this work, we found colocalization of laminin-5 and MMP-10, a phenomenon previously reported in squamous and basal cell cancers.…”
Section: Discussionmentioning
confidence: 54%
“…However, MMP-13 expression, a specific marker for malignant transformation in keratinocytes, 36,37 was detected in the epithelium of half of the keratoacanthomas studied. Thus, staining for MMP-13 protein does not assist in distinguishing keratoacanthomas from grade I SCCs 26 and suggests that at least a subset of keratoacanthomas cannot be classified as benign. Low expression of another collagenase, MMP-8, was found in the epithelium in three of the keratoacanthoma samples, whereas neutrophils stained positively in the majority of specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, among patients with a history and at high risk for skin cancer, regular screening is necessary to monitor the recurrence or persistence of the tumors. [1][2][3][4] At present, only a few specific biomarkers for cutaneous SCC have been identified, including STAT3, 44 E-cadherin, 45 and matrix metalloproteinases 13, 46 12, 47 and 7. 6,48 SerpinA1 has been previously suggested as a biomarker for the progression of insulinoma 49 and thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, the wide substrate specifity of MMP-13 suggests that it is also a powerful invasion tool for cancer cells. MMP-13 is one of the few MMPs primarily expressed by tumor cells in malignant tumors, such as breast carcinomas (Freije et al, 1994), squamous cell carcinomas (SCCs) of the head and neck (Airola et al, 1997;Johansson et al, 1997a), SCCs of the vulva (Johansson et al, 1999), and primary and metastatic melanomas (Airola et al, 1999;Nikkola et al, 2001). In SCCs of the head and neck and vulva, MMP-13 is expressed primarily by cancer cells at the invading edge of the tumor and the expression correlates with poor prognosis (Johansson et al, 1997a(Johansson et al, , 1999Cazorla et al, 1998).…”
Section: Introductionmentioning
confidence: 99%